2019
DOI: 10.3390/plants8070230
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Accurate and Fast Non-Destructive Single Leaf Area Model for Loquat (Eriobotrya japonica Lindl) Cultivars

Abstract: In this research, seven different models to predict leaf area (LA) of loquat (Eriobotrya japonica Lindl) were tested and evaluated. This species was chosen due to the relevant importance of its fruit as an appreciated early summer product and of its leaves and flower as a source of additional income within the nutraceutical and functional food markets. The analysis (calibration and validation) was made using a large dataset (2190) of leaf width (W), leaf length (L), and single LA collected in ten common loquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…For instance, data on leaf characteristics can be incorporated into databases [11,12] and employed to validate time-series quantification of leaf morphology (e.g., [13,14]) and to determine the performance of computer-assisted imaging systems and machine learning algorithms used to classify/recognize phenotypic traits of specific genotypes [15].Leaf area is generally measured with destructive or non-destructive methods [16], the latter often preferred as they are faster, cheaper, and non-invasive (i.e., no excision of leaves is required), therefore, permitting repeated and simultaneous measurements of LA and other physiological parameters (e.g., leaf gas exchange or fluorescence) on the same leaves.Collected information, such as leaf blade length (L) and width (W) [17][18][19][20][21][22][23][24][25] or the shape ratio of the leaf (L:W) [26], can be useful for characterizing leaf functions and structure, based only on proxy variables. In particular, the leaf shape ratio is of particular importance in horticultural sciences as it is regulated by several genetic factors and mutations [27], whose diversity can be analyzed in functional [28] and evolutionary terms [29].Thus far, numerous models have been proposed and applied with respect to both leaf (e.g., [20,30,31]) and shoot level [31-41] morphology of several fruit, vegetable, ornamental, medicinal, and aromatic crops [42]. Currently, LA models for aromatic and medicinal plants comprise several species such as basil, winter red Bergenia, or purple bergenia, calamint, coffee, cherry laurel, bush-willows, jimson weed, wild cucumber, horse-eye bean, lemon balm, peppermint, oleander, mountain mint, opium poppy, ground-cherry, or winter cherry, picrorhiza or kutka, saffron, sugar leaf, snowbell, summer snowflake, tea, common nettle, orange mullein [42], valeriana [43], and pepper plants [44].The world production of medicinal and aromatic plants (MAPs) is expected to rise up to 5 trillion US$ by 2050 [45].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, data on leaf characteristics can be incorporated into databases [11,12] and employed to validate time-series quantification of leaf morphology (e.g., [13,14]) and to determine the performance of computer-assisted imaging systems and machine learning algorithms used to classify/recognize phenotypic traits of specific genotypes [15].Leaf area is generally measured with destructive or non-destructive methods [16], the latter often preferred as they are faster, cheaper, and non-invasive (i.e., no excision of leaves is required), therefore, permitting repeated and simultaneous measurements of LA and other physiological parameters (e.g., leaf gas exchange or fluorescence) on the same leaves.Collected information, such as leaf blade length (L) and width (W) [17][18][19][20][21][22][23][24][25] or the shape ratio of the leaf (L:W) [26], can be useful for characterizing leaf functions and structure, based only on proxy variables. In particular, the leaf shape ratio is of particular importance in horticultural sciences as it is regulated by several genetic factors and mutations [27], whose diversity can be analyzed in functional [28] and evolutionary terms [29].Thus far, numerous models have been proposed and applied with respect to both leaf (e.g., [20,30,31]) and shoot level [31-41] morphology of several fruit, vegetable, ornamental, medicinal, and aromatic crops [42]. Currently, LA models for aromatic and medicinal plants comprise several species such as basil, winter red Bergenia, or purple bergenia, calamint, coffee, cherry laurel, bush-willows, jimson weed, wild cucumber, horse-eye bean, lemon balm, peppermint, oleander, mountain mint, opium poppy, ground-cherry, or winter cherry, picrorhiza or kutka, saffron, sugar leaf, snowbell, summer snowflake, tea, common nettle, orange mullein [42], valeriana [43], and pepper plants [44].The world production of medicinal and aromatic plants (MAPs) is expected to rise up to 5 trillion US$ by 2050 [45].…”
mentioning
confidence: 99%
“…Thus far, numerous models have been proposed and applied with respect to both leaf (e.g., [20,30,31]) and shoot level [31-41] morphology of several fruit, vegetable, ornamental, medicinal, and aromatic crops [42]. Currently, LA models for aromatic and medicinal plants comprise several species such as basil, winter red Bergenia, or purple bergenia, calamint, coffee, cherry laurel, bush-willows, jimson weed, wild cucumber, horse-eye bean, lemon balm, peppermint, oleander, mountain mint, opium poppy, ground-cherry, or winter cherry, picrorhiza or kutka, saffron, sugar leaf, snowbell, summer snowflake, tea, common nettle, orange mullein [42], valeriana [43], and pepper plants [44].…”
mentioning
confidence: 99%
“…Misgana et al (2018) preferred to use two traits for higher accuracy although it required more time on L and W measurements. Teobaldelli et al (2019) moderately suggested choosing the model according to its main purpose, i.e., for quick comparison or use as an estimation model.…”
Section: Propagation Of Talinum Paniculatum Using Stem Cuttingsmentioning
confidence: 99%
“…Measuring leaf area is fundamental for studying the photosynthetic efficiency of plants, determining biotic and abiotic damage to crops, analyzing growth, and estimating crop yield (Hosseini, McNairn, Merzouki, & Pacheco, 2015). The length and width of the leaf blade have been used to estimate the leaf area in fruit trees (Teobaldelli et al, 2019), vegetable crops (Padrón et al, 2016;Toebe et al, 2019), and ornamental crops (Fascella, Maggiore, Zizzo, Colla, & Rouphael, 2009;Giuffrida et al, 2011), among others.…”
Section: Introductionmentioning
confidence: 99%